2020
DOI: 10.1002/jcp.29618
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA HOXB‐AS3 exacerbates proliferation, migration, and invasion of lung cancer via activating the PI3K‐AKT pathway

Abstract: Lung cancer remains the leading cause of cancer-related death all over the world. In spite of the great advances made in surgery and chemotherapy, the prognosis of lung cancer patients is poor. A substantial fraction of long noncoding RNAs (lncRNAs) can regulate various cancers. A recent study has reported that lncRNA HOXB-AS3 plays a critical role in cancers. However, its biological function remains unclear in lung cancer progression. In the current research, we found HOXB-AS3 was obviously elevated in NSCLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 33 publications
(26 reference statements)
1
40
0
Order By: Relevance
“…In addition, in agreement with our data, Li Fan et al found that silence of PRRT3-AS1 suppresses the proliferation of PCa cells and boost their autophagy and apoptosis [15]. It is also suggested previously that, HOXB-AS3 shows tight association with the dismal prognosis for numerous cancer types [16][17][18]. The above findings suggest that, HOXB-AS3 and PRRT3-AS1 can be used to be the prognostic biomarkers for numerous cancer types.…”
Section: Plos Onesupporting
confidence: 92%
“…In addition, in agreement with our data, Li Fan et al found that silence of PRRT3-AS1 suppresses the proliferation of PCa cells and boost their autophagy and apoptosis [15]. It is also suggested previously that, HOXB-AS3 shows tight association with the dismal prognosis for numerous cancer types [16][17][18]. The above findings suggest that, HOXB-AS3 and PRRT3-AS1 can be used to be the prognostic biomarkers for numerous cancer types.…”
Section: Plos Onesupporting
confidence: 92%
“…lncRNA‐HNF1A‐AS1 facilitates gastric cancer cell invasion and migration through activating the PI3K/AKT pathway 35 . lncRNA HOXB‐AS3 accelerates cellular progression in lung cancer by activation of the PI3K/AKT pathway 36 . Our data reveal that circ‐PRMT5 knockdown suppresses the PI3K/AKT/mTOR pathway, whereas this inhibition effect was reversed by TCF7L2 up‐regulation.…”
Section: Discussionmentioning
confidence: 67%
“…Ye et al indicated that AC136475.3 can serve as a prognostic biomarker for patients with HCC who have cirrhosis (27). HOXB-AS3 has a dual role in various cancers; in colon cancer, it acts as a tumor suppressor, but in lung cancer, it acts as a tumor promoter (28,29). Zhong et al found that downregulation of lnc-EMA3B-AS1 may lead to a poor outcome in patients with HCC (30).…”
Section: Discussionmentioning
confidence: 99%